“Right Occupation” on the Middle Way in the Age of Thailand 4.0 - ชยทตฺโต, พระครูสังฆรักษ์ทรงพรรณ (Journal of Educational Review Faculty of Education in MCU, 2018)
“Right occupation” in accordance with the principles of nation development in the Age of Thailand 4.0, it may be classified into two levels. (1) Basic right occupation : it is to earn a living by following the rules of law and regulations or regulations, and (2) Advanced right occupation : it is a way of living that apart from carrying out the tasks of the law and the rules or regulations, also takes into account the moral responsibility or the discernment of the actions that are not contrary to good morals, too. And the occupations that do not into this category of two parts are all “wrong occupation”.